2006
DOI: 10.1152/ajpregu.00536.2005
|View full text |Cite
|
Sign up to set email alerts
|

Elevated hypothalamic orexin signaling, sensitivity to orexin A, and spontaneous physical activity in obesity-resistant rats

Abstract: lectively-bred obesity-resistant [diet resistant (DR)] rats weigh less than obesity-prone [diet-induced obese (DIO)] rats, despite comparable daily caloric intake, suggesting phenotypic energy expenditure differences. Human data suggest that obesity is maintained by reduced ambulatory or spontaneous physical activity (SPA). The neuropeptide orexin A robustly stimulates SPA. We hypothesized that DR rats have greater: 1) basal SPA, 2) orexin A-induced SPA, and 3) preproorexin, orexin 1 and 2 receptor (OX1R and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
139
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(156 citation statements)
references
References 56 publications
(74 reference statements)
14
139
1
2
Order By: Relevance
“…These data are consistent with the observation of greater SPA and NEAT in adult lean humans [9]. In addition, elevated SPA in 1- to 2-month-old OR rats [35] and higher resting energy expenditure in 10-year-old lean children [259] indicate that differences between SPA and energy expenditure between the lean and obese present early in life and track throughout adulthood. Together these data support the idea that elevated SPA and energy expenditure may confer obesity resistance in rats and humans.…”
Section: Role Of Neat In Obesity Resistancesupporting
confidence: 86%
See 4 more Smart Citations
“…These data are consistent with the observation of greater SPA and NEAT in adult lean humans [9]. In addition, elevated SPA in 1- to 2-month-old OR rats [35] and higher resting energy expenditure in 10-year-old lean children [259] indicate that differences between SPA and energy expenditure between the lean and obese present early in life and track throughout adulthood. Together these data support the idea that elevated SPA and energy expenditure may confer obesity resistance in rats and humans.…”
Section: Role Of Neat In Obesity Resistancesupporting
confidence: 86%
“…Specific mechanisms modulating energy expenditure and conferring obesity resistance to OR rats and perpetuating obesity in OP rats are currently under investigation. We showed that relative to OP and Sprague-Dawley rats, OR rats were significantly more responsive to the SPA-promoting effects of orexin-A [21, 35]. The mechanism mediating this increased sensitivity to orexin-A in OR rats is not yet defined, but we showed that OR rats had significantly greater orexin receptor gene expression relative to OP rats.…”
Section: Role Of Neat In Obesity Resistancementioning
confidence: 76%
See 3 more Smart Citations